The Role of Civic Education in Developing Critical Thinking Skills among English Language Education Students: A Literature Review - Kresensia Ine Kaka; Skolastika V. Gunu Keni; Felixita Engelina Beda; Fatimah Az Zahra; Alfret Benu (International Journal of Education, Information Technology, and Others, 2026)
Critical thinking is one of the essential competencies that university students must possess to face the challenges of 21st-century learning. For students of the English Language Education Study Program, critical thinking plays an important role in supporting academic success, decision-making, and the ability to analyze various information and issues objectively. Citizenship Education, as a compulsory course in higher education, has a strategic role in developing critical thinking skills through learning activities that emphasize the analysis of national issues, democracy, citizens’ rights and responsibilities, law enforcement, and social problem-solving. This study aims to analyze the existing literature on the role of Citizenship Education in developing the critical thinking skills of students in the English Language Education Study Program. The method employed in this study is a literature review, involving the collection and analysis of relevant scholarly articles, national and international journals, and other academic sources related to the research topic. The findings indicate that Citizenship Education contributes significantly to the enhancement of students’ critical thinking skills through learning activities that encourage analysis, evaluation, argumentation, reflection, and evidence-based decision-making. Furthermore, the critical thinking skills developed through Citizenship Education support learning processes in the English Language Education Study Program, particularly in understanding, evaluating, and communicating ideas in a logical and systematic manner. Therefore, Citizenship Education plays a significant role in fostering students’ critical thinking skills as an essential competency for academic achievement and active participation in society.